Meminimalisasi Nilai Error Peramalan dengan Algoritma Extreme Learning Machine - Rachmad Hidayat; Suprapto (Jurnal Optimasi Sistem Industri, 2012)
This study uses a machine learning algorithm which is the extreme model one of the new learning method of neural networks. Determining the value of forecasting based on actual value. Output generated more quickly in this process, because the learning done in a fast speed and better accuracy rate than conventional forecasting methods. Epoch using the parameter changes and changes in the range of accuracy of test results demonstrate the value of error is quite good during the system testing.